Pain and prosperity : reconsidering twentieth-century German history - Betts, Paul 1963- (Stanford Univ. Press, 2003)
Introduction: pain and prosperity in twentieth-century Germany / Greg Eghigian and Paul Betts -- Pain, entitlement, and social citizenship in modern Germany / Greg Eghigian -- Cities forget, nations remember: Berlin and Germany and the shock of modernity / Peter Fritzsche -- Purchasing comfort: patent remedies and the alleviation of labor pain in Germany between 1914 and 1933 / Patricia R. Stokes -- Modern pain and Nazi panic / Geoffrey Cocks -- The transformation of sacrifice: German identity between heroic narrative and economic sucess / Sabine Behrenbeck -- The myth of a suspended present: prosperity's painful shadow in 1950s East Germany / Katherine Pence -- Scarcity and success: the East according to the West during the 1950s / Ingrid M. Schenk -- Remembrance of things past: nostalgia in West and East Germany, 1980s-2000 / Paul Betts